QUALITY ASSURANCE PRACTICES IN SELECTED PRIVATE COLLEGES OF EDUCATION IN THE ASHANTI REGION, GHANA - Appau, A. R.; I.K., Agyei,; J., Adu-Agyem,; A., S., Owusu, (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This study aimed at investigating quality assurance practices in private colleges of education in the Ashanti Region of Ghana by examining the functions of quality assurance in selected private colleges of education, to determine the current level of collaboration between the administration of these colleges of education and the students and to recommend strategies for improving and monitoring quality assurance services to ensure their sustainability. The study examines how regulatory measures are not only designed to enhance the quality of private higher education institutions, but also how they impact the effort employed by private providers towards meeting quality assurance standards in the area in which they are located. The study involved 100 participants, consisting of five (5) Registrars, five (5) Dean of Students, five (5) Quality Assurance Heads, fifteen (15) lecturers, twenty (20) Administrators and fifty (50) students. Simple random and purposive sampling techniques were used in selecting the respondents. Questionnaires and interview guide were the main instruments used to collect data. The data were analysed with SPSS and Microsoft Excel. The respondents perceived that the role of quality assurance go a long way to help the private colleges of education to achieve their missions and visions. Also, they perceived that quality assurance raises the reputation of the colleges. The study concludes as regard how quality assurance helps private colleges of education in the Ashanti region, Ghana to achieve their visions and missions. Though the role of quality assurance is to help the universities to achieve their missions and visions, it is should be noted that it takes the collective and relentless effort of students, administrative and academic staff as well as management to achieve the desired standard of quality. It is recommended that private colleges of education in the Ashanti Region of Ghana should continue to use feedback from the periodic evaluation of courses to improve the quality of teaching and learning.